(untitled) (Olhar de Professor, 2022)
In this article, we discuss how the process of reflecting trainees on teaching practice occurs from the constitution of knowledge acquired by the master student in the school and academic contexts. For this, we seek to show, in Smyth’s (1991) perspective, the path of reflective movements carried out by the future teacher during the production of texts written in the Supervised Curricular Internship. The textual fragments analyzed were extracted from supervised internship reports and field diaries, made available for research at the Centro Interdisciplinar da Memória dos Estágios Supervisionados, at the Universidade Federal do Tocantins. This theoretical-analytical incursion of documentary nature points out that academics assume a reflexive posture as they record perceptions that integrate the set of information that contextualizes the contact with the school, with teachers, with Basic Education students and with the teaching environment teaching at the university.